2008
DOI: 10.2135/cropsci2007.10.0555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sugarcane × Saccharum spontaneum Progeny for Biomass Composition and Yield Components

Abstract: Saccharum spontaneum L. has contributed important traits to modern sugarcane (S. spp. L.) cultivars such as adaptation to environmental stress and ratooning ability. There is interest in further use of S. spontaneum in sugarcane improvement for sugar or energy‐from‐biomass production systems. In this study, parents and progeny from 43 biparental crosses between sugarcane and S. spontaneum clones were evaluated in field trials in China and Australia, along with several commercial cultivars. The S. spontaneum cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 13 publications
2
61
0
Order By: Relevance
“…The first is a type closer to the conventional sugarcane but comparatively presenting lower sucrose content and higher fiber content, whereas Type II has still higher fiber content and almost no sugar at all, and for that reason, to be used exclusively for biomass exploitation. In between those extremes, all distinct sucrose and fiber tradeoff is presented by a segregant population of a cross between ancestors (RAMDOYAL & BADALOO, 2007;WANG et al, 2008;SANTCHURN et al, 2012). Type I energy cane can be exploited by conventional sugar cane distilleries to produce first generation ethanol (EG1) from its juice, along with steam and electric power from the bagasse (ALEXANDER, 1985;RAO et al, 2007;MATSUOKA et al, 2014).…”
Section: Resumo: O Principal Interesse Na Cana Energia Reside Na Prodmentioning
confidence: 99%
“…The first is a type closer to the conventional sugarcane but comparatively presenting lower sucrose content and higher fiber content, whereas Type II has still higher fiber content and almost no sugar at all, and for that reason, to be used exclusively for biomass exploitation. In between those extremes, all distinct sucrose and fiber tradeoff is presented by a segregant population of a cross between ancestors (RAMDOYAL & BADALOO, 2007;WANG et al, 2008;SANTCHURN et al, 2012). Type I energy cane can be exploited by conventional sugar cane distilleries to produce first generation ethanol (EG1) from its juice, along with steam and electric power from the bagasse (ALEXANDER, 1985;RAO et al, 2007;MATSUOKA et al, 2014).…”
Section: Resumo: O Principal Interesse Na Cana Energia Reside Na Prodmentioning
confidence: 99%
“…Other studies conducted in sub-tropical countries have reported that there are high genetic correlations in biomass related traits making possible to use information from selection trials conducted in one country to anticipate or predict the behavior of the germplasm in another country (Wang et al 2008). However, the behavior of this germplasm varies importantly between tropical and sub-tropical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…and other species such as Saccharum spontaneum L. are conducted with the goal of moving desirable traits such as ratooning ability, growth vigor, cold tolerance and disease resistance from the wild relative to the breeding lines of conventional sugarcane (Wang et al 2008). Many of the resulting hybrids showed characteristics unwanted in the sugarcane industry such as a vigorous vegetative growth characterized by profuse production of thin and tall stalks, but with low sucrose production and accumulation ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…To properly evaluate sugarcane families, at least 10 to 20 clones per family are required [24]. Therefore, the families that had ≥15 clones were used in the present study to further investigate relationships between mean rust rating and % infection or rust severity.…”
Section: Correlations Of Mean Brown Rust Ratings With % Infection Andmentioning
confidence: 99%